Green Tea Polyphenol-Sensitive Calcium Signaling in Immune T Cell Function - Singh, Yogesh; Salker, Madhuri S.; Lang, Florian (Frontiers in Nutrition, 2021)
Polyphenol compounds found in Green tea have great therapeutic potential to influence multiple human diseases including malignancy and inflammation. In this mini-review, we describe the effects of green tea and the most important component EGCG in malignancy and inflammation. We focus on cellular mechanisms involved in the modification of T cell function by green tea polyphenol EGCG. The case is made that EGCG down-regulates calcium channel activity by influencing miRNAs regulating the expression of the channel at the post-transcriptional level.